Boosting singlet oxygen generation for salinity wastewater treatment through co-activation of oxygen and peroxymonosulfate in photoelectrochemical process - Qianqian Yang; Zhiyuan Feng; Yanbo Zhou; Hongying Zhao; Guohua Zhao (Fundamental Research)
High concentrations of inorganic ions in saline wastewater pose adverse effects on hydroxyl radical (HO•)-dominated technologies. Here, we report a unique strategy for boosting singlet oxygen (1O2) generation via coactivation of oxygen and peroxymonosulfate (PMS) by regulating the electron transfer regime in the photoelectrochemical process. The Fe-N bridge in atomic Fe-modified graphitic carbon nitride (denoted SA-FeCN) favors the construction of electron-defective Fe and electron-rich N vacancies (Nvs) to accelerate directional electron transfer. The produced intermediate (HSO4O···Fe−Nvs···OO) as a chemical channel accelerates the directional electron transfer from PMS to further reduce O2 to form activated products (SO5•−, O2•−), thereby transforming O2 into 1O2. An optimized 1O2 generation rate of 39.4 μmol L−1s−1 is obtained, which is 15.7–945.0 times higher than that in traditional advanced oxidation processes. Fast kinetics are achieved for removing various phenolic pollutants in a nonradical oxidation pathway, which is less susceptible to the coexistence of natural organic matter and inorganic ions. The COD removal for coal wastewater and complex industrial wastewater in real scenarios is found to reach a value of 90%-96% in 3 h. This work provides a new direction for boosting the 1O2 generation rate, especially for the selective degradation of target electron-rich contaminants in saline wastewater.